Surgical treatment of cerebellar metastases in elderly patients: A threshold that moves forward? - Stefano Telera; Roberto Gazzeri; Veronica Villani; Laura Raus; Francesca Romana Giordano; Alessandra Costantino; Catia Pompea Delfinis; Francesca Piludu; Isabella Sperduti; Andrea Pace (World Neurosurgery: X, 2023)
The impact of surgery for cerebellar brain metastases in elderly population has been the object of limited studies in literature. Given the increasing burden of their chronic illnesses, the decision to recommend surgery remains difficult.All patients aged ≥65 years, who underwent surgical resection of a cerebellar brain metastasis from May 2000 and May 2021 at IRCCS National Cancer Institute “Regina Elena”, were analyzed. The study cohort includes 48 patients with a mean age of 70.8 years. 7 patients belonged to the II Class according to the RPA classification, 41 to the III Class; the median GPA classification was 1.5. Median pre-operative and post-operative KPS was 60. Median Charlson Comorbidity Index (CCI) was 11; median 5-variable modified Frailty Index was 2. Overall, 14 patients (29%) presented perioperative neurologic and systemic complications. 34 patients (71%) were able to perform adjuvant therapies as RT and/or CHT after surgery. A higher CCI predicted complications occurrence (p = 0.044), while significant factors for a post-operative KPS ≥70, were i) hemispheric location of the metastasis, ii) higher pre-operative KPS, iii) RPA II classification. Median Overall Survival was 7 months. A post-operative KPS <70 (p = 0.004) and a short time interval between diagnosis of the primary tumor and cerebellar metastasis appearance, were predictive for a worse outcome (p = 0.012). Our study suggests that selected elderly patients with cerebellar metastases may benefit from microsurgery to continue their adjuvant therapies, although a high complications rate should be taken in account.